Improving fuel economy estimates on a chassis dynamometer using air conditioner correction factors - Reyes, Jose Alejandro M.; Quiros, Edwin N. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Carmakers, government regulatory agencies, and consumers share an interest in accurately determining a vehicle's fuel efficiency under operating conditions that match the expected use. Previous studies have shown that a vehicle's A/C system is the largest non-propulsive system in terms of energy usage and can therefore significantly reduce fuel economy. The fundamental objective of this study is to design and validate a new method of improving fuel economy estimates obtained on a chassis dynamometer, as a number of current laboratory testing methodologies, such as those applied in the Philippines, are typically run with the A/C system deactivated. The proposed methodology is based on the hypothesis that by measuring fuel economy penalty caused by the A/C system at different steady-state operating conditions, one can impose these penalties accordingly onto chassis dynamometer fuel economy results to obtain an estimate for fuel economy with the A/C system running. To test the validity of the proposed methodology, a test vehicle was outfitted with a data acquisition system and was driven 50 times around a predefined route using varying A/C system settings. The proposed method was then used to estimate fuel economy for each of the 50 runs. Comparing the calculated fuel economy with actual fuel economy showed an average absolute error of 1.924%. It was concluded that the proposed methodology is indeed a viable alternative to existing procedures.
Thesis (Master of Science in Mechanical Engineering)--University of the Philippines Diliman
Keywords: Automobiles -- Fuel consumption; Motor vehicles -- Air conditioning